Collaborative Governance in Athlete Development: Strengthening Synergy Between Local Government and KONI in the Riau Islands Province - Ode Harris; Edy Akhyari; Okparizan Okparizan (Social Science Academic, 2026)
This study analyzes the synergy between the Regional Government and the Indonesian National Sports Committee (KONI) in athlete development in the Province of the Riau Islands. The research focuses on collaborative governance in addressing problems such as limited sports facilities, inadequate funding, overlapping programs, and weak stakeholder coordination. The study applies the collaborative governance framework of Chris Ansell and Alison Gash, which includes starting conditions, institutional design, facilitative leadership, and collaborative processes. A qualitative descriptive method with a case study approach was employed. Data were collected through interviews, observations, and documentation involving the Youth and Sports Office, KONI administrators, coaches, and athletes. The findings reveal that collaboration has been implemented through training programs, competitions, talent development, and infrastructure support. However, the synergy remains less effective due to budget limitations, uneven infrastructure distribution, and insufficient coordination mechanisms. The study concludes that strengthening collaborative governance and stakeholder coordination is essential to improve sustainable athlete development and sports achievement in the Riau Islands Province.